Evaluation of emissions benefits of OBD-based repairs for potential application in a heavy-duty vehicle Inspection and Maintenance program. (15th February 2021) - Jiang, Yu; Yang, Jiacheng; Tan, Yi; Yoon, Seungju; Chang, Hung-Li; Collins, John; Maldonado, Hector; Carlock, Mark; Clark, Nigel; McKain, David; Cocker, David; Karavalakis, Georgios; et al.
Abstract: The implementation of a comprehensive heavy-duty vehicle (HDV) Inspection and Maintenance (I/M) program could be a critical element in ensuring the emission control effectiveness of diesel HDVs over their full useful life. An on-board diagnostics (OBD)-based I/M program could be a cost-effective emission reduction program for diesel HDVs. Forty-five vehicles equipped with selective catalytic reduction (SCR) with either the check-engine-light-on or malfunction-indicator-light (MIL)-on, or both, and in certain repairs categories, were identified and their emissions were measured before and after the repairs in this study. The post-repair nitrogen oxides (NOx) emissions decreased by 46%–75% for check-engine-light-on vehicles and by 53%–81% for MIL-on vehicles at different test speeds. NOx reductions for more than 55% of the vehicles showed reductions greater than 80% for at least one test speed. Pre-repair opacity readings from these HDVs were mostly lower than 5%, except for 6 vehicles that showed the opacity readings from 5.3% to 12.3%. After the repairs, opacity readings for all vehicles were below 5%, and average reductions of 43% in opacity were found for both check-engine-light-on and MIL-on cases. The testing results suggest that an OBD-based HDV I/M program would provide significant and tangible emission benefits. Graphical abstract: Image 1 Highlights: More than 45% of the tested vehicles showed NOx reductions greater than 80%. Vehicles with check engine light on had an average NOx reduction of 75% at 30 mph. Vehicles with malfunction indicator light on had an average NOx reduction of 81%. Fleet average reductions of 43% in opacity were found for SCR-equipped vehicles. The pre-repair opacity readings were 5% or less for all but 6 vehicles.